2017
DOI: 10.1002/jnr.24118
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane neurotoxicity in neonatal rats is related to an increase in the GABAAR α1/GABAAR α2 ratio

Abstract: Exposure of neonatal rat to sevoflurane leads to neurodegeneration and deficits of spatial learning and memory in adulthood. However, the underlying mechanisms remain unclear. The type A γ-aminobutyric acid receptor (GABA R) is a target receptor for sevoflurane. The present study intends to investigate the changes in GABA R α1/α2 expression and its relationship with the neurotoxicity effect due to sevoflurane in neonatal rats. After a dose-response curve was constructed to determine minimum alveolar concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…We selected the BWSQ2 scale because both sevoflurane and benzodiazepines cause addiction primarily through the activation of the γ-aminobutyric acid (GABA) A receptor. [ 6 , 15 17 ] A previous report also used the BWSQ2 scale to assess the withdrawal symptoms for propofol dependence, which activates the GABA A receptor. [ 18 ] In this case, there was a markedly shorter duration in the WS than the craving (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the BWSQ2 scale because both sevoflurane and benzodiazepines cause addiction primarily through the activation of the γ-aminobutyric acid (GABA) A receptor. [ 6 , 15 17 ] A previous report also used the BWSQ2 scale to assess the withdrawal symptoms for propofol dependence, which activates the GABA A receptor. [ 18 ] In this case, there was a markedly shorter duration in the WS than the craving (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Accumulated evidence indicates that sevoflurane induces neurodegeneration and apoptosis in vitro and vivo. [ 6 8 ] Neurons in the developing brain are specifically vulnerable to anesthetics, although the concentration of sevoflurane is 20-fold less than the recommended threshold values that induce apoptosis. [ 1 , 19 , 20 ] Second, there is a significant relationship between the rate of spontaneous abortion and occupational exposure to anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…WNK (with no lysine) kinases are Cl − -sensing kinases, including WNK1, that regulate the activities of NKCC1 and KCC2 [17] . In our previous study, we found that sevo urane's neurotoxicity on the developing brain was related to the changes in the transition of GABA A R a1 and a2 [18] . This neuronal damage was decreased by the NKCC1 inhibitor bumetanide [18] .…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies documented that sevo urane inhalation signi cantly aggravated cognitive de cits by initiating neuroin ammation and neurotoxicity in rat hippocampus [9]. Sevo urane administration triggers a series of pathophysiologic reactions comprising of mitochondrial dysfunction [10] and endoplasmic reticulum stress [11], and thereby results in cognitive dysfunction by inducing neuronal apoptosis [12], synaptogenesis impairment [13], and neuroin ammation [14].…”
Section: Introductionmentioning
confidence: 99%